Enterobacteriaceae opportunism isolated from Caspian Turtle Mauremys caspica (Gmelin, 1774) suffering from a fracture of the external shell, East of Al-Hammar Marshes, Iraq - Mohammad, Essa T.; Al-Shammari, Nadia A.H.; Bannai, Majid A.A. (Mesopotamian Journal of Marine Sciences, 2020)
Caspian Turtles Mauremys caspica (Gmelin, 1774) are classified as an endangered species on the IUCN red list, by a variety of dangers including hunting, deliberate killings and infectious diseases. The present report included the Opportunistic bacterial isolation which caused clinical signs on the M. caspica Turtles caught from the East Al-Hammar freshwater marshes, during summer 2017. It was suffering from a fracture of the external shell, tissue damage, bacterial growth and acute inflammation of the body tissues. The common clinical signs were external hemorrhage, histopathological changes revealed degeneration and necrosis in all organs associated with chronic inflammatory cell infiltration and Melanomacrophage cells were detected in all turtle tissues. The most common macroscopic lesions found on the skin of the turtle and ulcerative skin, the result in abscesses and dermatitis, regenerative changes on skin lesions and ulcerative deep necrotic and gangrenous changes in the turtle examined. Four different genera of family Enterobacteriaceae which identified by the VITEK II system, with a probability level of 94-99%, Citrobacter freundii (29.06%), Klebsiella oxytoca (25.58%), Serratia fonticola (24.41%) and Enterobacter cloacae (20.41%). The result showed that of a total of sixty-five bacterial isolates from the necrotic lesions skin tissue, some of them which are considered a potential threat to the public health.